PARTISIPASI WARGA PROLANIS KLINIK ”RAHMATIKA” GUNUNG PATI SEMARANG DALAM MENGGUNAKAN HAK PILIHNYA PADA PEMILIHAN KEPALA DAERAH - Muzayanah Muzayanah (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The constitutional system of the Republic of Indonesia is a democratic system, so the highest sovereignty rests in the hands of the people, so that the people have the power to determine the election of a leader who will occupy a chair of leadership in every region / region in the Republic of Indonesia. The right to vote is a human right that must be realized in accordance with the ideals of the Indonesian nation, as referred to in Pancasila and the 1945 Constitution. The patients who participate in the Prolanis Program at the Primary Clinic